2006
DOI: 10.1148/radiol.2382041053
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Iliac Stent Trial: Long-term Results in Patients Randomized for Primary or Selective Stent Placement

Abstract: Patients treated with PTA and selective stent placement in the iliac artery had a better outcome for symptomatic success compared with patients treated with primary stent placement, whereas data about iliac patency, ABI, and quality of life did not support a difference between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(64 citation statements)
references
References 29 publications
0
59
0
5
Order By: Relevance
“…The Dutch Iliac Stent Trial comparing stenting with balloon angioplasty and provisional stenting resulted in comparable clinical outcomes although this may have been caused by relatively low complexity TASC (TransAtlantic Society Consensus) A and B disease included in the trial. 25,26 Given the increased recoil seen with ostial iliac disease and risk of dissection with the more complex disease now more frequently encountered (ie, total occlusions, ulcerated or calcified lesions, and aneurysmal segments) the use of primary stenting for aortoiliac disease has increased. 27 A meta-analysis including 958 total patients with more complex aortoiliac disease found superior patency rates associated with primary stenting.…”
Section: Aortoilliac Diseasementioning
confidence: 99%
“…The Dutch Iliac Stent Trial comparing stenting with balloon angioplasty and provisional stenting resulted in comparable clinical outcomes although this may have been caused by relatively low complexity TASC (TransAtlantic Society Consensus) A and B disease included in the trial. 25,26 Given the increased recoil seen with ostial iliac disease and risk of dissection with the more complex disease now more frequently encountered (ie, total occlusions, ulcerated or calcified lesions, and aneurysmal segments) the use of primary stenting for aortoiliac disease has increased. 27 A meta-analysis including 958 total patients with more complex aortoiliac disease found superior patency rates associated with primary stenting.…”
Section: Aortoilliac Diseasementioning
confidence: 99%
“…Balloon-expandable stents (Palmaz; Johnson and Johnson Interventional Systems, which is stainless steel stent) were used in DIST. One-year patency rate of iliac stenting was roughly 90% [8]. A prospective, multicenter study stated that the balloon-expandable Assurant cobalt chromium iliac stent demonstrated sustained patency with obvious improvements.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the coating with polytetrafluorethylene (Teflon) has not been able to reduce hyperplasia response (20) . Comparative studies between the primary use of stents and utilization of stents in selected cases where catheter balloon angioplasty failed to show good outcomes (21) suggest that stenting should only be used in the iliac arteries, in case of failure of percutaneous transluminal angioplasty with catheter balloon. On the other hand, the type of material utilized in the composition of the stents utilized in the present study -stainless steel and nitinol -did not present differences as far as neointimal hyperplasia is concerned.…”
Section: Discussionmentioning
confidence: 99%